Peningkatan Hasil Belajar Siswa melalui Media Buku Cerita Bergambar pada Pembelajaran IPAS di SD Negeri Tamansari 1 Yogyakarta - Novaria Rahmawati; Marwanti, Endah; Ardhian, Trio; Lestari, Inastuti (Indonesian Journal of Learning and Educational Studies, 2024)
This article is a development (R&D) with the 4D (Four-D) development model. This study aims to, explain the design of picture storybook media development in learning IPAS of grade V students of SD Negeri Tamansari Yogyakarta, explain the feasibility of picture storybook media development products in learning IPAS of grade V students of SD Negeri Tamansari 1 Yogyakarta, explain the learning outcomes of students by using picture storybook media in learning IPAS of grade V students of SD Negeri Tamansari 1 Yogyakarta. The research subjects were fifth grade students of Tamansari I Yogyakarta Elementary School with a total of 26 students. The object of this research is an illustrated storybook of IPAS subject CHAPTER 7 “My Region is My Pride”. The design process of developing picture storybooks is carried out with 4 stages, namely, the define stage, the design stage, the development stage, the disseminate stage. Feasibility assessment for IPAS subject picture storybook products “CHAPTER 7 My Regional Pride”, product feasibility assessment conducted by media experts, material experts, and class teachers. The use of learning media with picture storybooks gets a better class average than before using picture storybooks. picture story learning media is effective to be applied for elementary school student learning. Before using the average value of student learning outcomes 80.58 and after using picture story media has increased quite well, namely 86.54. This means that picture story books can improve student learning outcomes more effectively and well.